2013
DOI: 10.1137/130906842
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and Permittivity Image Reconstruction at the Larmor Frequency Using MRI

Abstract: • Magnetic Resonance Electrical Property Tomography (MREPT) aims to visualize both conductivity σ and permittivity ǫ distributions at the Larmor frequency (≈ 128 MHz for a 3 T MRI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…We confirmed that the result of the proposed method improves when we obtained H − in addition to H + from the simulation and used both to give the normal derivative of E z based on Eq. (18). The method to obtain both H + and H − by multichannel surface coils in addition to the quadrature birdcage coil is referred to in [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that the result of the proposed method improves when we obtained H − in addition to H + from the simulation and used both to give the normal derivative of E z based on Eq. (18). The method to obtain both H + and H − by multichannel surface coils in addition to the quadrature birdcage coil is referred to in [14].…”
Section: Resultsmentioning
confidence: 99%
“…The first approach is to solve the PDE using an iterative optimization calculation [18]- [21]. In these iterative methods, it is important to give the optimal initial value, without which a local minimum solution can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In Serralles et al, the above‐mentioned LMT was converted to a forward problem, now called ‘global Maxwell tomography’. Based on Song and Seo, Ammari iteratively minimized the mismatch between the forward model and observed data starting with an initial guess by solving Equation for the complex H + . This method was further developed by Palamodov …”
Section: Advanced Reconstruction Techniquesmentioning
confidence: 99%
“…Another MREPT method ( 22 ) was proposed on the basis of the fact that the magnetic field near the center of a birdcage or a transverse electromagnetic coil is homogeneous along its central axis ( 23 , 24 ), and it is assumed that the contribution of the along-axis component of the magnetic field is negligible when the region of interest is close to the center of the coil. A first-order PDE including a gradient term of the unknown EP was formulated via properly manipulating Maxwell equations, and the gradient term describes the inhomogeneity of the object under investigation.…”
Section: Introductionmentioning
confidence: 99%